Pendampingan Implementasi Projek Penguatan Profil Pancasila pada Anak Usia Dini Di Kecamatan Abiansemal - Suryaningsih, Ni Made Ayu; Cahaya, I Made Elia; Endah Poerwati, Christiani (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Widya Sari Kindergarten and Widya Kumara Kindergarten are early childhood education institutions or PAUD under the Swadarma Karya Foundation, Darmasaba Village, Abiansemal. The two institutions have played an important role in the advancement of early childhood education in Darmasaba village since 1975 until now. In facing the challenges of future developments, the two institutions always try to keep abreast of the changes that occur, especially related to the development of science and technology, including the implementation of the new